Building Bridges Between the Clinic and the Laboratory: A Meeting Review – Brain Malformations: A Roadmap for Future Research - Sapir, Tamar; Barakat, Tahsin Stefan; Paredes, Mercedes F.; Lerman-Sagie, Tally; Aronica, Eleonora; Klonowski, Wlodzimierz; Nguyen, Laurent; Ben Zeev, Bruria; Bahi-Buisson, Nadia; Leventer, Richard; Rachmian, Noa; Reiner, Orly (Frontiers in Cellular Neuroscience, 2019)
In the middle of March 2019, a group of scientists and clinicians (as well as those who wear both hats) gathered in the green campus of the Weizmann Institute of Science to share recent scientific findings, to establish collaborations, and to discuss future directions for better diagnosis, etiology modeling and treatment of brain malformations. One hundred fifty scientists from twenty-two countries took part in this meeting. Thirty-eight talks were presented and as many as twenty-five posters were displayed. This review is aimed at presenting some of the highlights that the audience was exposed to during the three-day meeting.